Optimal control design for reducing vertical acceleration of a motor yacht form. (1st December 2018) - Cakici, Ferdi; Yazici, Hakan; Alkan, Ahmet Dursun
Abstract: Ship motions and their adverse effects have always been studied with the aim of reducing motions and accelerations using whatsoever plausible ways during both the ship design process and operating lifetime. In the present work, a simulation study is carried out by taking into consideration the passengers in several locations of the selected motor yacht in an intermediate sea state with Hs = 1 m. Irregular head wave scenario at Fn = 0.25 is investigated and a controller design is implemented to ensure that the calculated RMS vertical acceleration values are decreased to tolerated levels in terms of motion sickness index. First, wave loads are obtained in the time domain by using strip theory, linear superposition technique, and the most common realization technique. Then, using a linear two-degree-of-freedom mathematical model, in which pitch and heave motions are considered together with the direct solution of convolution integrals, the uncontrolled motions and accelerations are obtained. Then, the linear matrix inequalities based on robust static output feedback controller are designed to mitigate the vertical acceleration of the ship. Finally, the results obtained with the robust static output feedback control design are presented in numerical simulation studies to demonstrate the effectiveness of the proposed control approach. Highlights: Cummins' equation is used for the mathematical model in irregular waves. Direct solution of the convolution integral is used for fluid memory effects. It is aimed to mitigate vertical ship motions by designing a robust controller. The results obtained with the static output feedback controller are presented.